A Stereodynamic Redox‐Interconversion Network of Vicinal Tertiary and Quaternary Carbon Stereocenters in Hydroquinone–Quinone Hybrid Dihydrobenzofurans. Issue 46 (18th October 2018) - Storch, Golo; Kim, Byoungmoo; Mercado, Brandon Q.; Miller, Scott J.
Abstract: Reversible redox processes involving hydroquinones and quinones are ubiquitous in biological reaction networks, materials science, and catalysis. While extensively studied in intermolecular settings, less is known about intramolecular scenarios. Herein, we report hydroquinone–quinone hybrid molecules that form two‐stereocenter dihydrobenzofurans via intramolecular cyclization under thermodynamic control. A π‐methylhistidine peptide‐catalyzed kinetic resolution allowed us to study the stereodynamic behavior of enantio‐ and diastereo‐enriched dihydrofurans. In the course of this study, it was revealed that a reversible intramolecular redox‐interconversion network connects all four possible stereoisomers via inversion of a quaternary carbon stereocenter without achiral intermediates. As a result, these findings on hydroquinone‐quinone hybrid molecules provide insights into potential natural origin and synthetic access of the common dihydrobenzofuran motif. Abstract : Reversible intramolecular redox‐interconversion in hydroquinone–quinone hybrid dihydrobenzofurans is the key to a dynamic four‐state network. Peptide‐mediated kinetic resolution via acylation allowed the interconversion pathways to be studied in detail and mechanistic insights to be obtained.